2016
DOI: 10.18632/oncotarget.13085
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric superiority of flattening filter free beams for single-fraction stereotactic radiosurgery in single brain metastasis

Abstract: For single-fraction stereotactic radiosurgery (SRS) using linac in brain metastases, more accurate treatment delivery with higher tumor absorbed doses and lower absorbed doses to normal tissues remains an enormous challenge. The purpose of this study was to investigate the dosimetric superiority in flattening filter free beams (FFF) for volumetric modulated arc therapy (VMAT) in single brain metastasis. 68 patients with single brain metastasis were included in this study. Every patient was subjected to VMAT tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
2
12
1
Order By: Relevance
“…This study aimed to build on the work by Lai et al 11 , Rieber et al 10 and Laoui et al 15 by evaluating 10 MV FFF alongside 6 MV FFF for single fraction intracranial SRS specifically using non-coplanar dynamic conformal arcs compared to a 6 MV flattened beam. The FFF option on modern linacs is appealing to use for high dose single fraction treatments due to the increased dose rate which can reduce treatment times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed to build on the work by Lai et al 11 , Rieber et al 10 and Laoui et al 15 by evaluating 10 MV FFF alongside 6 MV FFF for single fraction intracranial SRS specifically using non-coplanar dynamic conformal arcs compared to a 6 MV flattened beam. The FFF option on modern linacs is appealing to use for high dose single fraction treatments due to the increased dose rate which can reduce treatment times.…”
Section: Discussionmentioning
confidence: 99%
“…9 Several authors have investigated the use of 6 MV FFF for SRS treatments mostly using volumetric arc therapy (VMAT) and have shown that a significant reduction in beam-ontime (BOT) and improved dose gradients are achievable with comparable conformity. [10][11][12] Abacioglu et al have compared 10 MV FFF non-coplanar VMAT for a Varian TrueBeam linac to GammaKnife treatments for 12 patients with either vestibular schwannoma or cavernous sinus meningioma. The results showed that 10 MV FFF VMAT was comparable in terms of coverage, homogeneity and organ at risk (OAR) sparing with some gains in treatment efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…There are many treatment techniques for multiple brain metastases, each with its own characteristics . In this study, we compared six plans including CK, IMRT, VMAT, NC1, NC3 and NC5.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a lower peripheral dose is a unique characteristic in FFF beams due to the decrease of photon head scatter, head leakage and leaf transmission [38]. It has been demonstrated that the dose gradients in FFF beams were superior to FF beams and that FFF provides further brain sparing compared to traditional techniques for SRS in single brain metastasis [39,40].…”
Section: Contouring and Treatment Planning Srsmentioning
confidence: 99%